(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2011)
The road to graduates The road to top corporate brass ha t studies. With shift of interest_ to_ managem;e flooded business globalization, foreign_ m_vest?rs h_:h cheap skilled man deals to a country lt e India,_ w1 I d to a demand for ower. This economic paradigm e . ore management institutes which necess r,ly es not roduce quality and talent. We must look mto t is as a erious matter as this leads to concentration o a (arge chunk of youth opting for management long w1th it e need to inspect and monitor the qualt of educa_t1on provided and modify them if need be. It 1s emphasized that the Management Institutes have to gear Uf! themselves for improving quality, have to abandon thetr short-sighted and fire-fighting approaches, and adopt a policy of continuous improvement.